Implementasi Kurikulum Merdeka Belajar di SMP Negeri 1 Talawaan - Deisye Supit; Danny A Masinambow; Heidi Kristian Repi; Orbanus Naharia; Suzan N H Jacobus (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Merdeka Belajar Curriculum is one of the newest education policies in Indonesia aimed at improving the quality of education at all levels, including Junior High School (SMP). This article will discuss the implementation of the Merdeka Belajar Curriculum in SMP by looking at the changes that have occurred in three main aspects, namely curriculum, learning, and assessment. The research method used is a case study of SMP Negeri 1 Talawaan. The results show that the Merdeka Belajar Curriculum has undergone significant changes in terms of more flexible and integrated learning, holistic assessment, and increased student participation in the learning process.